2022
DOI: 10.1111/pcmr.13059
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma central nervous system metastases: An update to approaches, challenges, and opportunities

Abstract: Brain metastases are the most common brain malignancy. This review discusses the studies presented at the third annual meeting of the Melanoma Research Foundation in the context of other recent reports on the biology and treatment of melanoma brain metastases (MBM). Although symptomatic MBM patients were historically excluded from immunotherapy trials, efforts from clinicians and patient advocates have resulted in more inclusive and even dedicated clinical trials for MBM patients.The results of checkpoint inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Melanoma metastases to the CNS rank third in frequency, just after lung and breast metastases, and are also the ones with the worst prognosis, with just six months of survival after diagnosis. 1 , 2 , 3 , 4 Some studies have reported an incidence of metastasis to the CNS in patients diagnosed with melanoma of 10%–40%, with higher incidences of up to 90% in post-mortem studies, and in most cases, are multiple lesions that can affect one or more cerebral lobes and, in a lower percentage of cases, unique circumscribed lesions. 5 , 6 , 7 There is controversy regarding the factors that predispose to developing CNS metastases in patients with cutaneous melanoma and their survival with conventional treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma metastases to the CNS rank third in frequency, just after lung and breast metastases, and are also the ones with the worst prognosis, with just six months of survival after diagnosis. 1 , 2 , 3 , 4 Some studies have reported an incidence of metastasis to the CNS in patients diagnosed with melanoma of 10%–40%, with higher incidences of up to 90% in post-mortem studies, and in most cases, are multiple lesions that can affect one or more cerebral lobes and, in a lower percentage of cases, unique circumscribed lesions. 5 , 6 , 7 There is controversy regarding the factors that predispose to developing CNS metastases in patients with cutaneous melanoma and their survival with conventional treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Further, suppression of MAPK signaling often leads to feedback or compensatory activation of the PI3K/AKT pathway(4-7). Unfortunately, drug combinations that inhibit both the MAPK and PI3K pathways are poorly tolerated in patients, and clinically efficacious doses have not been achieved (8)(9)(10)(11)(12). Although simultaneous inhibition of the MAPK and PI3K pathways is generally toxic, there is no evidence that the proximal molecular causes of that toxicity are the same in normal and in cancer tissues.…”
Section: Introductionmentioning
confidence: 99%